PENGARUH PERSEPSI HARGA, CITRA MEREK DAN PROMOSI TERHADAP KEPUTUSAN KONSUMEN DALAM MEMILIH JASA GOJEK DI KECAMATAN TAMAN KABUPATEN SIDOARJO - Muttaqin, Muhammad Zukhruful; Kartini, Ida Ayu Nuh (JEM17: Jurnal Ekonomi Manajemen, 2020)
In the competition to obtain consumer purchasing decisions, several factors that can be considered are price perception, brand image and promotion. The purpose of this research is in accordance with what is stated in the formulation of the problem, namely to determine the role of Price Perception, Brand Image and Promotion in influencing Consumer Decisions in choosing Gojek as online transportation. The study was conducted in Taman District, Sidoarjo Regency. Sampling was done by distributing online questionnaires of 100 respondents. This research uses quantitative research. The analysis technique used is multiple linear regression analysis techniques to test hypotheses. The results in this study indicate that Price Perception does not have a significant effect on Purchasing Decisions with a value of t arithmetic 0.547 smaller than t table (1.98498), while Brand Image (t arithmetic = 2.577) and Promotion (t arithmetic = 5.129) have significant influence on Purchasing Decisions. However, Price Perception, Brand Image and Promotion simultaneously influence the Purchasing Decision with the acquisition of a significance value of 0.00.